Politik Uang dalam Pemilu Legislatif Dapil I Kabupaten Kupang 2024: (Studi kasus Desa Oeltua, Kecamatan Taebenu, Kabupaten Kupang) - Gloria Stephanie D.L Sair; Rex Tiran; Yeftha Yerianto Sabaat (Amandemen: Jurnal Ilmu pertahanan, Politik dan Hukum Indonesia, 2025)
This thesis is entitled "Money Politics in the Legislative Election for Electoral District I, Kupang Regency 2024" (case study of Oeltua Village, Taebenu District, Kupang Regency). The problem studied is how money politics occurs in Oeltua Village and who are the actors involved in money politics, in the 2024 Kupang Regency Electoral District I legislative election. The aim of this research is to describe and analyze money politics in the 2024 Kupang Regency legislative election. The location of this research was carried out in Oeltua Village, Taebenu District, Kupang Regency. This research is a qualitative descriptive analysis research to describe or illustrate the influence of money politics on community participation. Data collection techniques in this research used interviews and documentation.The results of this research show that Money Politics has an influence on the participation of the people who receive it, but it is actually not a certainty in obtaining votes in accordance with the funds spent by legislative candidates in voting in elections, this is caused by several factors that make money politics ineffective, namely the wrong money politics strategy, a successful team that is not qualified in selecting legislative candidates, which makes money politics not guarantee that it can buy votes from voters who receive gifts in the form of money